Analysis of FSI effects for a novel WEC using high-fidelity simulations - John Jawahar Edwin, Jason Ebenezer (My University, 2022)
Wave energy is more reliable and continuous in time, compared to solar and wind energy which are more periodic. The World Energy Council predicts that wave energy has the potential to meet 10-20% of the world’s energy demands. A wave energy converter (WEC) as the name suggests, harvests energy from the vertical motion of waves. The WEC is anchored in an offshore location, using mooring lines attached to the sea floor. The generated electricity is transmitted to a grid on-land, since the WEC does not have an energy storage system, to keep the weight of the WEC low. In this project, a WEC is studied using the commercial CFD code STARCCM+. The WEC is designed by Novige AB called NoviOcean 500. The primary objective is to study the forces acting on the surface of the buoy as a result of the heave, surge and pitch motions, which affect the power generation and the stability of the buoy in the waves. It is equally important to study the mooring line forces of the WEC, for design estimations of the mooring line material and size. A mesh independence study is done to ensure the results of the study are mesh independent. The different wave generation models, the fifth order Stokes wave and irregular wave models are considered, with the irregular wave model being found more suited for short sea states, like stormy sea conditions. And the fifth order Stokes wave more uniform and regular in nature. Various wave parameters which affect the heave motion of the WEC, like wavelength and wave period are studied. A nominal wave period between 5-9 seconds is used to depict normal sea wave conditions. Finally, the linear spring and catenary coupling models are used to study the differences in heave motion, coupling elongation and coupling forces. From the thesis work, it is concluded that the use of the fifth order Stokes wave model, with a wave period of between 5-9 seconds and a catenary coupling model for the mooring lines, is a good simulation setup for the study of the NoviOcean 500.
Keywords: WEC, buoy, CFD, wave energy, mooring, overset mesh, fluid structure interaction; buoy; CFD; wave energy; mooring; overset mesh; fluid structure interaction